2008
DOI: 10.1159/000143391
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Inflammation and <i>Staphylococcus aureus</i> Colonization of Involved Skin of Atopic Dermatitis Patients

Abstract: Atopic dermatitis (AD) is a multifactorial chronic inflammatory disease mainly stemming from a genetic predisposition that leads to hypersensitivity to environmental factors and a common involvement of Staphylococcus aureus (SA) colonization. The aim of this work was to propose a new non-invasive approach to enumerate the genes coding for the toxins of SA in atopic skin samples. In parallel, the study aimed to evaluate the change in AD through 3 markers of the inflammatory response: IL-8, IL-1RA/IL-1α and IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 65 publications
2
33
1
2
Order By: Relevance
“…Involucrin expression is significantly decreased in both acute and nonlesional skin of subjects with AD compared with skin from healthy subjects 15. Furthermore, all the inflammatory markers induced in the present in vitro model of stimulated NHK have been shown to be upregulated in AD, for example, TSLP and IL-18 cytokines 25,30…”
Section: Discussionmentioning
confidence: 69%
“…Involucrin expression is significantly decreased in both acute and nonlesional skin of subjects with AD compared with skin from healthy subjects 15. Furthermore, all the inflammatory markers induced in the present in vitro model of stimulated NHK have been shown to be upregulated in AD, for example, TSLP and IL-18 cytokines 25,30…”
Section: Discussionmentioning
confidence: 69%
“…Moreover, to obtain data on the cascade of events occurring during rosacea, we have used assay methods that enabled us to collect mRNA of key genes from an epidermal extract obtained after micro‐abrasion and proteins on the skin surface (as IL‐8) by swabbing .…”
Section: Discussionmentioning
confidence: 99%
“…Using full thickness skin models, S. aureus strain LUH14616 was shown to induce the release of the inflammatory chemokine IL-8 by epidermal keratinocytes [29]. Although no much is known about the role of IL-8 in AD, its up-regulation in AD was shown to be associated with the presence of S. aureus [16]. We have found that the S. aureus-induced IL-8 response by epidermal models was not affected by FLG-KD, but significantly enhanced following exposure to IL-31, suggesting that enhanced S. aureus colonization alone due to FLG-KD is not sufficient to evoke an inflammatory response and requires the presence of (AD-related) cytokines such as IL-31.…”
Section: Discussionmentioning
confidence: 99%